Catalytic Synthesis of Liquid Hydrocarbons - Xolliyev Shamsiddin Xudoyberdiyevich; Murodov Rustam Murodovich (Genius Journals, 2022)
Aromatic hydrocarbons, mainly benzene, toluene, ethylbenzene and xylene, are the most important chemicals in the petrochemical industry. Currently, aromatic compounds are obtained by catalytic reforming and cracking of petroleum fractions. As oil reserves shrink, the demand for alternative sources of aromatics increases. One of the alternative sources of aromatic hydrocarbons are natural and biogases. Dehydroaromatization reactions under non-oxidizing conditions on bentonite catalysts containing modified intermediate metal ions is a promising method for using natural and petroleum gases [1-6]. Natural gas containing mainly methane is thermodynamically stable and resistant to many reagents. The binding energy C − H in a methane molecule is 439 kJ/mol. Direct synthesis of methane is difficult, but its derivatives are more active than methane, they enter into chemical reactions well [7-12]. The reactions proceed in the presence of a catalyst which accumulates zeolite. The oxidizing agent is not involved in this process. [13-15]. Based on the above, the purpose of this work is the synthesis of environmentally friendly liquid fuels by direct catalytic aromatization of natural gas
Keywords: methane; aromatic hydrocarbons; catalyst; bentonite catalysts